Modern industrial statistics : with applications in R, MINITAB and JMP - Kenett, Ron S., & Zacks; Zacks, Shelemyahu (Hoboken, NJ, USA : Wiley, 2021)
"Industrial Statistics is concerned with maintaining and improving the quality of goods and services. It involves a broad range of statistical tools but maintaining and improving quality is its main concern. Variability is inherent in all processes, whether they be manufacturing processes or service processes. This variability must be controlled to create high quality goods and services and must be reduced to improve quality. Industrial Statistics focuses on the use of statistical thinking, i.e., the appreciation of the inherent variability of all processes in order that all possible outcomes can be assessed. It also focuses on developing skills for modeling data and designing experiments that can lead to improvements in performance and reductions in variablity"
Includes bibliographical references and index.
Keywords: Reliability (Engineering) -- Statistical methods; Quality control -- Statistical methods